ANALISIS PENDEKATAN TERPADU DAN BERPIKIR KREATIF TERHADAP KEMAMPUAN KOMUNIKASI ILMIAH PESERTA DIDIK - Kurniawan Kurniawan; Achyani Achyani; Hening Widowati (Universitas Muhammadiyah Metro, 2020)
Abstract: The purpose of this study is to see the effect of integrated approaches and creative thinking on students' scientific communication skills. The expected benefits of this study are to get creative thinking and have scientific communication skills for students in learning. The design of this study was pre-experimental with a literature review. Research results obtained based on literature review include: Learning with an integrated approach can improve students' creative thinking skills; Creative thinking skills can be improved by brainstorming and guided inquiry learning and can facilitate students in scientific communication, thus it is concluded that learning with an integrated approach can develop students' scientific communication skills.